Exercise addiction in college students: the impact of body dissatisfaction, stress, physical activity and gender - Ying Wang; Guohuan Hua; Wenting Liu; Changsheng Wan; Ming Hao; Mingshou Zhang (Frontiers in Psychiatry)
IntroductionEngaging in physical activity is commonly regarded as beneficial to health. However, exercise addiction may arise when enthusiasm for exercise reaches a level that disrupts life balance and overall well-being. Factors influencing college students’ exercise addiction remain largely unknown.MethodsParticipants aged 18–23 years (N = 384) underwent body measurements, and sex-adapted silhouettes were employed to assess their level of body dissatisfaction. The Exercise Addiction Inventory was used to investigate the level of exercise addiction among college students. We used t-tests to compare sex differences in BMI, body fat percentage, body dissatisfaction levels, stress levels, and exercise addiction among college students. Chi-square’s test was used to compare differences between males and females in terms of BMI, physical activity levels, stress, and exercise addiction ratings. The exercise addiction level of college students was used as the dependent variable in multiple regression analysis, and BMI, muscle mass, body fat percentage, exercise score, stress level score, and body dissatisfaction level score were used as predictors.ResultsThe results of multivariate regression analysis revealed sex differences in physical activity scores, stress levels, body dissatisfaction, and exercise addiction levels, with males consistently exhibiting significantly higher scores than females. In males, body dissatisfaction scores and stress were significant predictors of exercise addiction. Among females, physical activity scores, stress, body dissatisfaction, and body fat percentage were identified as significant predictors of exercise addiction.DiscussionCollege students confront risks in relation to exercise addiction. High stress levels and body dissatisfaction may be important causes of exercise addiction. The male students had higher body dissatisfaction, stress levels, and risk of exercise addiction than the female students. With a change in female bodily aesthetics in terms of a shift from a primary focus on thinness-related beauty to having a thin and toned body, the risk of exercise addiction in female college students may increase.